2015
DOI: 10.1002/cplx.21673
|View full text |Cite
|
Sign up to set email alerts
|

A novel neural network based on NCP function for solving constrained nonconvex optimization problems

Abstract: This article presents a novel neural network (NN) based on NCP function for solving nonconvex nonlinear optimization (NCNO) problem subject to nonlinear inequality constraints. We first apply the p-power convexification of the Lagrangian function in the NCNO problem. The proposed NN is a gradient model which is constructed by an NCP function and an unconstrained minimization problem. The main feature of this NN is that its equilibrium point coincides with the optimal solution of the original problem. Under a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Table reports the comparison results in terms of solution, CPU time, and l 2 ‐norm error with four different initial points. It can be seen that the proposed neural network not only has a better performance in solution accuracy but also has faster convergence rate than the models in Xia et al () and Effati and Moghaddas (). It is also found that the Xia et al's model is unstable and can not solve this example.…”
Section: Simulation Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Table reports the comparison results in terms of solution, CPU time, and l 2 ‐norm error with four different initial points. It can be seen that the proposed neural network not only has a better performance in solution accuracy but also has faster convergence rate than the models in Xia et al () and Effati and Moghaddas (). It is also found that the Xia et al's model is unstable and can not solve this example.…”
Section: Simulation Resultsmentioning
confidence: 88%
“…The proposed neural network , Xia et al's model , and the Effati and Moghaddas's model are compared in Table in terms of solution, CPU time, and l 2 ‐norm error with four different initial points. From Table , it can be observed that the proposed neural network has a better performance in convergence time than the models in Xia et al () and Effati and Moghaddas (). It is also seen that the proposed model is more accurate in terms of solution and l 2 ‐norm error than other models.…”
Section: Simulation Resultsmentioning
confidence: 89%
See 3 more Smart Citations